2021
DOI: 10.1126/sciadv.abh3592
|View full text |Cite
|
Sign up to set email alerts
|

An outsized role for the Labrador Sea in the multidecadal variability of the Atlantic overturning circulation

Abstract: Labrador Sea forcing can dominate multidecadal AMOC variability even while contributing minimally to mean circulation strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
61
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 44 publications
(97 reference statements)
12
61
0
Order By: Relevance
“…To further validate whether the decadal AMOC variation in SRST is consistent with the mechanism proposed by Yeager (2020) that emphasizes the importance of AMOC lower limb in decadal prediction, we examine the LF co-evolution of AMOC( 𝐴𝐴 𝐴𝐴 2 ) and sea surface height (SSH). Consistent with Yeager (2020) that the deep flow associated with decadal AMOC variations can induce an SSH response which is critical in sustaining decadal prediction skill, the zonal-averaged SSH anomalies in the western SPNA, where LF AMOC variability originates (Yeager et al, 2021), show a similar evolution pattern between FOSI and SRST (see Figure S6 in Supporting Information S1). They both show a delayed SSH response to the change in AMOC( 𝐴𝐴 𝐴𝐴 2 ) lower limb, suggesting that in both FOSI and SRST the deep circulation changes are driving the upper ocean circulation changes as reasoned by Yeager (2020) and recently validated in an eddy-resolving coupled simulation (Yeager et al, 2021).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…To further validate whether the decadal AMOC variation in SRST is consistent with the mechanism proposed by Yeager (2020) that emphasizes the importance of AMOC lower limb in decadal prediction, we examine the LF co-evolution of AMOC( 𝐴𝐴 𝐴𝐴 2 ) and sea surface height (SSH). Consistent with Yeager (2020) that the deep flow associated with decadal AMOC variations can induce an SSH response which is critical in sustaining decadal prediction skill, the zonal-averaged SSH anomalies in the western SPNA, where LF AMOC variability originates (Yeager et al, 2021), show a similar evolution pattern between FOSI and SRST (see Figure S6 in Supporting Information S1). They both show a delayed SSH response to the change in AMOC( 𝐴𝐴 𝐴𝐴 2 ) lower limb, suggesting that in both FOSI and SRST the deep circulation changes are driving the upper ocean circulation changes as reasoned by Yeager (2020) and recently validated in an eddy-resolving coupled simulation (Yeager et al, 2021).…”
Section: Resultssupporting
confidence: 81%
“…In contrast, HIST shows the strongest transport with 26.8 Sv. In general, the high detrended LF standard deviations (STDs) fall into two regions in all simulations: one in the lighter water class representing the upper limb and the other in the denser water class representing the lower limb where the southward denser currents carry the long‐lasting predictive memory (Yeager, 2020; Yeager et al., 2021). The location and magnitude of the lower limb STD in SRST are similar to those in FOSI, both occurring in a denser water class (>36.875σ2 ${\sigma }_{2}$) than in HIST (>36.775σ2 ${\sigma }_{2}$).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing LR, HR and observed MLD, Chang et al (2020) showed LR contains large positive bias in the north Atlantic deep water formation regions such as Labrador Sea (see their Figure 15). MLD bias there may affect deep water formation and AMOC variability (Yeager et al, 2021). Exploring the impacts of MLD and deep water formation on AMOC is beyond the scope of this work.…”
Section: Associations With Amocmentioning
confidence: 99%
“…However, the exact role of the Irminger and Labrador Sea in AMOC variability is still controversial. In particular, it is discussed whether deep water formation in the Labrador Sea contributes only marginally to AMOC variability (Desbruyères et al, 2019;Li et al, 2021;Menary et al, 2020), whether there has been a shift in deep water formation from the Labrador to the Irminger Sea over the past decade (Rühs et al, 2021), or whether deep water formation in the Labrador Sea dominates multidecadal AMOC variability, while formation in the Irminger Sea influences high-frequency variability (Yeager et al, 2021).In the Irminger Sea, strong surface heat and momentum fluxes were found to be most important for generating density anomalies in the boundary currents, such as the East Greenland-Irminger Current (EGIC) or over the Reykjanes Ridge (LeBras et al, 2020;Petit et al, 2020). Based on OSNAP, a light mode convective water named upper Irminger Sea Intermediate Water (uISIW; σ θ = 27.65-27.73 kg m −3 ) has been identified forming at the edge of the EGIC (LeBras et al, 2020).…”
mentioning
confidence: 99%